2018
DOI: 10.1039/c8cc03311k
|View full text |Cite
|
Sign up to set email alerts
|

Single-site labeling of lysine in proteins through a metal-free multicomponent approach

Abstract: We report a chemoselective and site-selective approach that distinguishes one Lys from its multiple copies, N-terminus, and other competitors. The phospha-Mannich protocol works with multiple proteins and installs probes without structural and functional perturbations. It delivers an antibody-drug conjugate with selective anti-proliferative activity towards HER2 expressing SKBR3 breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…[11][12][13] In parallel, site-selective chemical strategies for the conjugation of native and natural proteins have also flourishedo ver the past few years, giving rise to methods targeting varioust ypes of amino acids (for example, lysine, cysteine, tryptophan, tyrosine) that proved to be effective on proteins of all sizes, including antibodies. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] With the aim of pursuing the efforts in this field, we could not help but notice that the vast majority of previously reported strategies for the site-selective conjugation of native proteins were focusedo nt he modificationo faunique residue. We hypothesized that targeting two different amino acid side chainss imultaneously would lower the enormouss ubset of possibilities given by single-residue bioconjugation techniques, thus increasing our chances of developing as ite-selective method by minimising the number of potentially reactive sites;apath that has also been successfully explored by others in the meantime.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In parallel, site-selective chemical strategies for the conjugation of native and natural proteins have also flourishedo ver the past few years, giving rise to methods targeting varioust ypes of amino acids (for example, lysine, cysteine, tryptophan, tyrosine) that proved to be effective on proteins of all sizes, including antibodies. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] With the aim of pursuing the efforts in this field, we could not help but notice that the vast majority of previously reported strategies for the site-selective conjugation of native proteins were focusedo nt he modificationo faunique residue. We hypothesized that targeting two different amino acid side chainss imultaneously would lower the enormouss ubset of possibilities given by single-residue bioconjugation techniques, thus increasing our chances of developing as ite-selective method by minimising the number of potentially reactive sites;apath that has also been successfully explored by others in the meantime.…”
Section: Introductionmentioning
confidence: 99%
“…74 Expanding the substrate tolerance of such DNAzymes from peptides to proteins is a further challenge, but worth undertaking considering the difficulty inherent to achieving nonenzymatic site-selective Lys modification of native proteins. [59][60][61][62][63][64][65] We are currently pursuing such experiments.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 One such reaction is lysine (Lys) acylation, where Lys acetylation is critical for histones and in other contexts, [27][28][29][30] and many longer-chain Lys acylation PTMs [31][32][33] such as malonylation, 34,35 succinylation, 34,36 and glutarylation 37,38 have been discovered yet are poorly understood. 39 As an alternative to approaches that include introduction of Lys analogues, [40][41][42][43] nonsense codon suppression, [44][45][46][47][48][49] bottom-up ligation-based assembly strategies, [50][51][52] or enzymatic methods that typically require creation of a non-native protein by insertion of a specific target sequence, [53][54][55][56][57][58] DNAzymes are promising for top-down introduction of Lys acylation PTMs onto intact native proteins, [59][60][61][62][63][64][65] but only if DNAzymes can be identified with the fundamental catalytic ability of Lys acylation.…”
Section: Introductionmentioning
confidence: 99%
“…Later, we demonstrated that a metal‐free phospha‐Mannich reaction could enable the single‐site labeling of lysine (Scheme c) . The chemoselective reaction of an aldehyde with all the accessible primary amines results in imines.…”
Section: Single‐site Labeling Of Native Proteinsmentioning
confidence: 99%
“…[107] Later, we demonstrated that a metal-free phospha-Mannich reaction could enable the single-site labeling of lysine (Scheme 12c). [108] The chemoselective reaction of an aldehyde with all the accessible primary amines results in imines. Here, the N-terminus imine forms imidazolidinone creating the opportunity for phosphorus-centered nucleophile to render siteselective modification of lysine.…”
Section: Labeling Of Lysinementioning
confidence: 99%